2005
DOI: 10.1097/01.prs.0000182224.98761.cf
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Fetal Constraint Induces Chondrocyte Apoptosis and Premature Ossification of the Cranial Base

Abstract: These experiments confirm the ability of intrauterine constraint to induce changes in the morphology and cell biology of the cranial base in synostotic fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Graham and Smith described two cases of metopic synostosis believed to be the result of limited space for the fetal head (one was jammed in a bicornuate uturus, the other one between the legs of his two siblings) [34]. More recently this theory was supported by Smartt et al, proving the principle in a mouse model [90].

Intrinsic brain malformation

…”
Section: Etiologymentioning
confidence: 99%
“…Graham and Smith described two cases of metopic synostosis believed to be the result of limited space for the fetal head (one was jammed in a bicornuate uturus, the other one between the legs of his two siblings) [34]. More recently this theory was supported by Smartt et al, proving the principle in a mouse model [90].

Intrinsic brain malformation

…”
Section: Etiologymentioning
confidence: 99%
“…Craniosynostosis has an incidence of approximately 1 in 2500 live births, and may be syndromic or isolated (Mooney et al, 1998;Ridgway and Weiner, 2004;Smartt et al, 2005;Ferreira et al, 2006;Kobus et al, 2007;Maltese et al, 2007;Di Rocco et al, 2009;Mackenzie et al, 2009;Kolar, 2011). It can cause intracranial hypertension, and, in syndromic cases, morbidity may be increased further due to exophthalmos, obstructive airway disease, and other comorbidities (Kapp-Simon et al, 2005;Di Rocco et al, 2009;Scott et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…They demonstrated that mechanical forces caused by intrauterine cerclage up-regulates TGF-ß1 in osteoblasts of the involved cranial suture and downregulates its dural TGF-ß3 4,6 . This phenomenon associated to chondrocyte apoptosis was also seen in the spheno-occipital synchondrosis, suggesting morphologic skeletal changes in the cranial base sutures 7 . These experimental studies corroborate other clinical studies which suggest that non syndromic forms of craniosynostosis might have started in the primary premature fusion of the cranial base sutures [8][9][10][11] .…”
Section: Discussionmentioning
confidence: 84%